The use of Artificial Intelligence (AI) tool by lecturers in the teaching and learning of English language in Federal College of Education (Technical) Omoku and Federal College of Education (Technical) Umunze - Augusta Chiedu Assimonye; Chinasa Florence Okoh (Journal Majelis Paspama, 2024)
In recent years, the integration of Artificial Intelligence (AI) in education has transformed how teachers and students interact with learning materials. However, in many teacher education institutions in Nigeria, the use of AI tools in language instruction remains limited and uneven. Lecturers often rely on traditional methods, which restrict students’ exposure to innovative learning technologies that could enhance writing, grammar, comprehension, and communication skills. This gap raises concern about how effectively lecturers are adopting AI to support English Language teaching and learning in Colleges of Education. The study used a descriptive survey design to explore how lecturers and students perceived the use of artificial intelligence in teaching English Language. It was conducted in the Federal Colleges of Education (Technical) at Omoku in Rivers State and Umunze in Anambra State, involving forty-four participants—seventeen lecturers and twenty-seven final-year students. Data were collected through a validated and reliable structured questionnaire analyzed using mean and standard deviation to determine agreement levels on issues relating to AI use in English Language education. The results revealed that lecturers moderately used artificial intelligence (AI) tools in teaching English Language in the Federal Colleges of Education (Technical) at Omoku and Umunze. Findings showed strong agreement that AI supported grammar and punctuation correction (Mean = 3.57, SD = 0.78) and provided instant feedback on assignments (Mean = 2.96, SD = 0.52). The grand mean (3.02, SD = 0.74) indicated moderate adoption. Similarly, AI usage extent was modest (Grand Mean = 2.64, SD =.085), mainly in grammar (Mean = 2.50) and listening comprehension (Mean = 2.60), suggesting gradual but growing integration. The study concluded that while AI has begun to improve teaching effectiveness, its application remains limited. It recommended increased institutional support, lecturer training, and infrastructure development to promote full AI integration in English Language education.